Assessing synergies between soil research in the Republic of Ireland and European Union policies - H. Binner; L. Andrade; M.E. McNamara (Environmental Challenges, 2024)
Recent policies on soil in Europe are shifting towards sustainability, climate goals, and a holistic approach to soil quality. In line with these policy changes, research on Irish soils is also changing: the historical primary focus on agriculture, linked to Ireland's economic reliance on agriculture, is being supplanted by policies focussed on soil quality. Here, we perform a systematic review of recent research on Irish soils and of how this research aligns with key elements of the European Soil Strategy (ESS) for 2030. Our results show that the dominant natural setting within each county does not always determine the research focus. Instead, the research focus in each county is driven by the national emphasis on funding of major environmental research centres and by the strength of Ireland's agricultural sector. Our results also show that most publications are small in scale, typically reporting data on < 30 samples. Importantly, the most common parameters analysed vary among study settings. Publications in agricultural settings include analyses of more soil parameters than those from non-agricultural settings, but typically lack data quality indicators (e.g., standard reference materials, duplicates and/or analytical replicates). In non-agricultural settings, publications often include analyses of soil metal concentrations, but not other important parameters such as total porosity and soil nutrients. Overall, soil pH is the most common parameter assessed in all settings, while soil organic carbon, soil moisture and soil porosity are the least common. Our data also reveal a lack of a standard soil classification system, due, in part, to differences in soil classification systems used among scientific fields. Benchmarking current research on Irish soils against the ESS highlights key knowledge gaps. Resolving this issue is critical to Ireland's ability to address future challenges relating to soil protection, reuse, monitoring, restoration, remediation, and the maintenance of soils for healthy water resources.